Indicadores técnicos e comerciais da Empresa Sementes Oilema - Levinski, Paulo Afonso (2012)
Oilema Seeds Company is located in the West Bahia and works with soybean seed production. Founded in 1998, has a strong presence in the market where it operates. Therefore, this study aimed to assess the technical and commercial company indicators. Were analyzed indicators such as field use (AC), incoming efficiency (RR), processing efficiency (EB), damage and losses (IQT), index disposal of batches (IDL), commercialization efficiency (EC) and Technical and Commercial Efficiency (ETC). In the period under study, it was found that production areas have increased while field utilization levels decreased, but preserving the direction of strategies to ensure quality. Besides the high-tech into production and processing, innovations in the commercial area were developed, in order to strengthen the Oilema Seeds trademark.